The Oxford handbook of biblical studies - Rogerson, J. W.; Lieu, Judith (Oxford University Press, 2008)
Part I: On the discipline -- Part II: Languages, translation, and textual transmission of the Bible -- Part III: Historical and social study of the Bible -- Part IV: The composition of the Bible -- Part V: Methods in biblical scholarship -- Part VI: The interpretation of the Bible -- Part VII: The authority of the Bible.